Curcumin and metformin‐mediated chemoprevention of oral cancer is associated with inhibition of cancer stem cells. Issue 11 (13th July 2017) - Siddappa, Gangotri; Kulsum, Safeena; Ravindra, Doddathimmasandra Ramanjanappa; Kumar, Vinay V.; Raju, Nalini; Raghavan, Nisheena; Sudheendra, Holalugunda Vittalamurthy; Sharma, Anupam; Sunny, Sumsum P.; Jacob, Tina; Kuruvilla, Binu T.; Benny, Merina; et al.
Abstract : Effective chemoprevention is critical for improving outcomes of oral cancer. As single agents, curcumin and metformin are reported to exhibit chemopreventive properties, in vitro as well as in patients with oral cancer. In this study, the chemopreventive efficacy of this drug combination was tested in a 4‐nitro quinoline‐1‐oxide (4NQO) induced mice oral carcinogenesis model. Molecular analysis revealed a cancer stem cell (CSC)‐driven oral carcinogenic progression in this model, wherein a progressive increase in the expression of CSC‐specific markers ( CD44 and CD133 ) was observed from 8th to 25th week, at transcript (40‐100‐fold) and protein levels ( P  ≤ 0.0001). Chemopreventive treatment of the animals at 17th week with curcumin and metformin indicated that the combination regimen decreased tumor volume when compared to the control arm (0.69+0.03 vs 6.66+2.4 mm 3 ; P  = 0.04) and improved overall survival of the animals ( P  = 0.03). Assessment of the molecular status showed an overall downregulation of CSC markers in the treatment arms as compared to the untreated control. Further, in vitro assessment of the treatment on the primary cells generated from progressive stages of 4NQO‐induced mice tissue showed a concordant and consistent downregulation of the CSC markers following combination treatment ( P  < 0.05). The treatment also inhibited the migratory and self‐renewal properties of these cells; the effect of which was prominent in the cultures of early dysplastic tissue ( P  < 0.002). Collectively, our observations suggest that the combination of curcumin and metformin may improve chemopreventive efficacy against oral squamous cell carcinoma through a CSC‐associated mechanism.